2009
DOI: 10.26634/jet.6.2.799
|View full text |Cite
|
Sign up to set email alerts
|

Learners' Perceptions Toward Online Learning: An Application For A Synchronous E-Class

Abstract: The aim of this study is to discover the effects of an e-class application on the computer and reading anxiety of learners, and the correlation between the two anxieties. The learners' perceptions of this new learning experience are also investigated. Information was obtained by using the Foreign Language Reading Anxiety Scale (FLRAS), the Computer Anxiety Scale (CAS) and learners' diaries. The study found that both anxieties decreased at the end of the application. A positive relationship between both types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(11 reference statements)
0
3
0
1
Order By: Relevance
“…Yuzer et al. (2009) reported that shy students felt more comfortable expressing their opinions in the online environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuzer et al. (2009) reported that shy students felt more comfortable expressing their opinions in the online environment.…”
Section: Resultsmentioning
confidence: 99%
“…Webcams seem crucial here, as students were negative about the lack of non-verbal cues in online discussions, with Erickson et al, (2020) reporting this meant discussion did not flow as well as in classroom setting. Yuzer et al, (2009) reported that shy students felt more comfortable expressing their opinions in the online environment. However, some students felt disconnected and overwhelmed by multitasking.…”
Section: • Online Interaction Between Tutor and Studentmentioning
confidence: 99%
“…Computer technology is highly related to the success of the e-learning environment (Li & Lee, 2016). For example, Yuzer et al (2009) found that computer literacy reduced the learners' level of anxiety through the use of visual support (pictures, graphs, tables etc) which helped them with the comprehension of the reading material. Also, the learners' participation was increased in virtual classes as each learner had the same amount of time to answer the instructors' questions.…”
Section: Synchronous Learning Before the Covid-19 Pandemicmentioning
confidence: 99%
“…Las investigaciones han buscado cómo se puede reducir la ALE a través de entornos de aprendizaje electrónico (p. ej., JoohaeKim, 2005;Yuzer et al, 2009), teléfonos móviles (p. ej., Rahimi & Soleymani, 2015), entornos de comunicación mediada por computadora (p.…”
Section: Revisión De La Literaturaunclassified